PENDIDIKAN KELUARGA BERBASIS BUDAYA LOKAL: STUDI SOSIOLOGI PADA MASYARAKAT NEGERI HUKURILA, KECAMATAN LEITIMUR SELATAN - Feky Manuputty; Simona Christina Hendrika Litaay; Afdhal Afdhal; Nathalia Debby Makaruku (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This study aims to explore the role of local culture in family education within the community of Negeri Hukurila, Leitimur Selatan District. The research employs a qualitative approach using observation and in-depth interviews to reveal how local cultural values such as pela, gandong, masohi, sasi, and adherence to customary laws form the foundation of family education. The findings show that family education not only emphasizes knowledge but also integrates the social and cultural norms of Maluku. These values contribute to the creation of harmonious families that are economically, socially, and culturally prosperous. This educational process is embodied through the bina keluarga program, an initiative of the Protestant Church of Maluku (GPM), which in Hukurila is carried out routinely every day. The novelty of this study lies in the discovery that the Bina Keluarga Program, although initiated by the church, has been adopted and consistently implemented in daily life, reinforcing the role of families in education based on local culture.